STRATEGI KOMUNIKASI KEBUN BINATANG KASANG KULIM DALAM MENGELOLA OBJEK WISATA - Andrew Alexander; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Kasang Kulim Zoo is the only zoo located in Riau province. This makes Kasang Kulim Zoo have great potential as both a tourist destination and an animal education tourism. To maximize both aspects, effective communication is crucial in the management of Kasang Kulim Zoo. The aim of this research is to determine the strategies for selecting communicators, selecting communicants, composing messages, and communication channels for Kasang Kulim Zoo. This research utilizes a qualitative research method. The research subjects consist of six individuals selected through purposive technique. The informants include 6 individuals: 1 manager of Kasang Kulim Zoo, 2 zoo guides at Kasang Kulim Zoo, 1 MC at Kasang Kulim Zoo, and 2 visitors to Kasang Kulim Zoo. Data collection is done through interviews, observations, and documentation, while data analysis involves data reduction, data conclusion, data presentation, drawing conclusions, and evaluation using data validity techniques such as prolonged engagement and triangulation. The results of this research indicate that the communication strategy implemented by Kasang Kulim Zoo in managing the tourist attraction involves selecting communicators who have credibility and good communication skills. The selection of communicants is done only by guides and the MC, based on the visitors' age. The message composition strategy involves delivering informative and persuasive messages. The communication channels chosen by Kasang Kulim Zoo include face-to-face interaction, the use of speakers, information boards inside and outside the zoo area, as well as social media platforms such as Instagram and TikTok. Keywords: Communication strategy, Management, Kasang Kulim Zoo